Nuevas tecnologías y formación permanente del profesorado de educación de adultos - Ángel GARCÍA DEL DUJO; Antonio Víctor MARTÍN GARCÍA; María Dolores PÉREZ GRANDE (Ediciones Universidad de Salamanca, 2016)
In this paper, a concrete case of application and use of the New Technologies for the permanent formation  of adult education teachers is presented. The authors, after referring to the scientific assumptions underlying the programme, present the reasons why it is applied to adult education professionals; then, they make a presentation of the design, structure and functioning of the programme, which is not conceived as a single course with a beginning and an end, but as a formation network promoting shared reflection on real and specific situations and educational actions carried out by adult educational professionals. The authors wish to emphasize the collaboration between researchers and professionals from different regions and countries, and also the increase in the metacognition level of Adult Education Professionals about their own performance and formative process.